Analisis Kompetensi Profesional, Pedagogik, Sosial dan Kepribadian Mahasiswa - Jofri Boimau; Nani Mediatati (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2020)
The purpose of this research is to describe the level of mastery of professional, pedagogical, personal and social competency of PPKn college student who carry out an internship program III at SMKN 2 & 3 Salatiga. This type of research is descriptive research. Data collection techniques using document studies, interviews, and observations. Data analysis techniques using quantitative descriptive techniques. The research subjects were 7 college student of PPKn Internship III Participants. The results showed the level of mastery of pedagogical and professional competencies of PPKn college student as apprentice III participants who were shown the ability to compile lesson plans, implement lesson plans in class categories in both good and very good categories, with an average score of 3.02 to 3.97. The mastery of 7 competency indicators was assessed, 4 college student were rated very well with an average score of 4, and 3 college student on indicators 4 and 7 were rated well with a score of 3, the average was also 3.71 the category was very good. 5 indicators of social competency were assessed, 4 college student rated very good, the average score of 4 and 3 college student on indicators 3 and 4 were rated as good with a score of 3, the average was 3.80, the category was very good. The results of the study can be concluded mastery of teacher competency, college student who carry out an internship program III on average are very good at carrying out tasks as a prospective professional teacher.